2023
DOI: 10.1186/s43065-022-00068-z
|View full text |Cite
|
Sign up to set email alerts
|

Passive buildings: a state-of-the-art review

Abstract: Passive buildings are proving to be a solution to menaces of energy crisis and greenhouse gas emissions across the world. Such buildings tend to exhibit low energy demand owing to their cleverly designed envelopes, which comprise of walls, roofs, doors, windows and other openings. This requires use of new materials and technology, leading to an increased initial construction cost. However, with reduced energy consumption, the lifecycle cost of a passive building may be lower than that of a conventional buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“…The results obtained from University College London indicate that the overall capital cost uplift for the development of a new passive building was only 0.9%, taking into account the life cycle costs [69]. Similarly, in [21], it was observed that passive buildings are likely to have a lower cost during their design life due to a lower energy consumption and a carbon footprint compared to traditional buildings. However, based on the experience of the authors and the information collected during meetings with passive house experts, in the author's opinion, the above-mentioned estimations from the literature concern exemplary, high-quality passive building projects, which were successfully completed without the occurrence of unwanted events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from University College London indicate that the overall capital cost uplift for the development of a new passive building was only 0.9%, taking into account the life cycle costs [69]. Similarly, in [21], it was observed that passive buildings are likely to have a lower cost during their design life due to a lower energy consumption and a carbon footprint compared to traditional buildings. However, based on the experience of the authors and the information collected during meetings with passive house experts, in the author's opinion, the above-mentioned estimations from the literature concern exemplary, high-quality passive building projects, which were successfully completed without the occurrence of unwanted events.…”
Section: Resultsmentioning
confidence: 99%
“…Besides this, developing passive buildings enables the achievement of EU energy policy goals connected with the European Green Deal. In addition, passive buildings are affordable as their higher initial cost results in a lower cost during their design life due to lower energy consumption and a carbon footprint compared to traditional buildings [21]. Last but not least, the concept of a passive building is based on building physics, so it cannot fail, and meeting the heating, cooling, and primary energy demand of a building is checked in computer programs (e.g., the Passive House Planning Package (PHPP) dedicated to PHs) before its realization phase.…”
Section: Literature Review 21 Requirements and Benefits Connected Wit...mentioning
confidence: 99%
“…Recent studies worldwide have noted a signifi cant reduction in energy consumption, ranging from 30% to 50%, attributed to modifi cations in building envelopes. These changes include improvements like thermal insulation in roofs and walls, external walls and roofs with shading, the incorporation of overhangs and wing walls in windows, as well as the use of refl ective-coated glass for window glazing, (Anand, et al 2023).…”
Section: Building Envelope Improvementsmentioning
confidence: 99%
“…The Internet of Things enables the development of a flexible system architecture that uses sensor data to improve the efficiency of passive buildings. On the other hand, the practical design of an IoT sensor network for a specific building still relies on the knowledge and experience of a diverse team of experts [18] . In Passive House sensor networks: Human-centric thermal comfort, this project aims to make Passive Houses (PH) more comfortable for people.…”
Section: Findingmentioning
confidence: 99%